The Influence Of Workload And Compensation On Employee Performance LPI Foundation Al-Muttaqin Tasikmalaya City - Mohammad Zaldhi Rizkiandi; Dian Indiyati (International Journal of Economics, Business and Innovation Research, 2024)
Education has a crucial role in the development of the quality of human resources and can improve the economy which can have a positive influence on the development of a country. This can affect the progress of human resources, including in an agency in educational institutions such as the Al-Muttaqin Foundation Islamic Education Institution (LPI) in Tasikmalaya City. Therefore, the success of an educational institution agency will be more optimal if it has competent and qualified human resources. This study examines workload, compensation, and employee performance at LPI Al-Muttaqin Foundation as well as the effect of workload and compensation on employee performance. Using a quantitative approach with questionnaires distributed to 110 employees at LPI Al-Muttaqin Foundation Tasikmalaya City through the saturated sample method, the data were analyzed using descriptive and path analysis with IBM SPSS version 23. The results showed that workload and employee performance fell into the "very good" category, while compensation fell into the "good" category. There is a significant influence both partially and simultaneously on workload and compensation on employee performance. The total effect of workload and compensation on employee performance is 58.8% and 41.2% is influenced by other factors.